Anaerobic wastewater treatment to yield biogas - Zainol, Norazwina; Rahman, Rakmi Abd. (Penerbit Universiti Sains Malaysia, 2004)
Anaerobic treatment of industrial wastewater has became a viable technology in recent years due to the rapid development of high-rate reactors, such as anaerobic filter, upflow anaerobic sludge blanket (UASB) (Fang et al., 1996; Dinsdale et al., 1997) both upflow and downflow stationary packed beds (Nebot et al., 1995), and fluidized or expanded beds (Chen et al., 1988; Breintenbucher et al., 1990; Hickey et al., 1991; Iza, 1991; Perez et al., 1997a; Seckler et al., 1996). This development is due to the fact that the method combines a number of significant advantages, including low energy consumption, low excess sludge production and enclosure of odours.